PHYSICAL PROPERTIES OF WOUND HEALING GEL OF ETHANOLIC EXTRACT OF BINAHONG (Anredera cordifolia (Ten) Steenis) DURING STORAGE. - Sri Hartati Yuliani; Achmad Fudholi; Suwijiyo Pramono; Marchaban . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Binahong (Anredera cordifolia (Ten) Steenis) has been used as wound healing in traditional Indonesian medicine. The developing of the dosage forms using the formulation technology approach has been done. The aim of this study was to examine the physical properties of the wound healing gel of ethanolic extract of binahong during storage. The factorial design method 3 factors and 2 levels was employed to achieve this study. The three factors used in this study were Carbopol, CMC-Na and Caalginate with low and high level for each factor. The physical properties of the wound healing gel of ethanolic extract of binahong was evaluated on day 1, 30, 60 and 90 for viscosity and bioadhesion study. The result showed that CMC-Na and Caalginate increased the alteration of physical properties of wound healing gel of ethanolic extract of binahong during storage. The carbopol maintained the physical properties of the gel during storage.Key words: bioadhesion, binahong, viscosity, wound healing gel.